Non-markovian electron tunneling in SARS-CoV-2 virus infection in structured environments - Muhammad Waqas Haseeb; Mohamad Toutounji (PLoS ONE, 2026)
The role of non-Markovian quantum effects in biological processes is increasingly recognized, yet remains largely unexplored in virology. This study investigates the influence of quantum tunneling on SARS-CoV-2 infection dynamics, focusing on the interaction between the viral spike protein and the host ACE2 receptor. We employed the non-Markovian quantum state diffusion (NMQSD) to model electron transfer mediated by vibrational modes within the structured lipid membrane. Our results challenge conventional semiclassical models by demonstrating that this interaction operates not in the weak coupling limit, but in an intermediate coupling regime where quantum coherence is pivotal. We find that specific vibrational modes significantly enhance tunneling efficiency and sustain coherence over extended timescales. Furthermore, our findings reveal a critical dependence on resonance: tunneling is highly efficient below resonance via resonance-assisted mechanisms, whereas tunneling rates decrease sharply above resonance due to decoherence effects. These results, which parallel coherence phenomena in photosynthesis, suggest that the host’s membrane environment actively optimizes electron transfer. This work presents a new paradigm for virus-host interactions and identifies the modulation of vibrational frequencies as a potential new avenue for antiviral drug design.